Profile of cytokines in aqueous humor and trabecular meshwork cell culture in patients with pseudoexfoliation glaucoma - V. V. Rakhmanov; A. V. Yuryeva; T. S. Varganova; D. I. Sokolov; S. V. Chepanov; K. L. Markova; Yu. S. Astakhov; S. Yu. Astakhov; S. A. Selkov (Медицинская иммунология, 2021)
Glaucoma is one of the leading causes of irreversible blindness worldwide, being an age-related disease. Its pathogenesis still is not fully understood. A particular interest is attracted to evaluation of the cytokine concentrations in the trabecular meshwork cell culture, and in the aqueous humor (AH) taken from the same patient, since such data may allow to describe more completely the glaucomatous trabecular changes and to clarify the mechanisms of intercellular interactions in pseudoexfoliative (PEX) glaucoma. The purpose of this study was a comparative analysis of cytokine contents in AH and in trabecular tissue (TT) supernatants in the patients with PEX glaucoma. The study included 23 eyes of patients with PEX glaucoma. The material studied was AH and supernatant of TT cell culture. The cytokine concentration was measured using a flow cytofluorimeter FacsCantoII (BD, USA) using the CBA method. SPSS version 19 software (IBM, USA) was used for the statistical data processing. Concentrations of cytokines (TNFα, IFNγ, IL-1β, IL-6, IL-8, IL- 10, VEGF, GM-CSF) were determined in AH and in the TT supernatant for each of the patients with PEX glaucoma. Only IL-6 and VEGF concentrations in AH were higher than those in the TT supernatant in patients with PEX glaucoma. The IL-6 concentration positively correlated with the VEGF and IL-8 concentrations in the TT supernatant. Correlations between other cytokines in the TT supernatant and AH were also identified and analyzed. Multiple regression analysis revealed that the duration of glaucoma and the IFNγ and TNFα concentrations in AH may have a significant influence on the corneal endothelial cells, being associated with density reduction in patients with PEX glaucoma. The correlation analysis did not reveal any links between other clinical data (corneal thickness in the optical center, IOP level, age) and the cytokine concentrations in the studied tissues. The obtained results suggest that only simultaneous analysis of the cytokine concentrations in the TT supernatant and AH taken from the same patient may provide a more complete description of the cytokine imbalance and pathological processes occurring in the trabecular meshwork in PEX glaucoma patients. It has been shown that the changing cytokine ratios observed in PEX glaucoma may be associated with development of uniform structural and functional changes in all tissues of the anterior eye segment.